Early childhood development: an imperative for action and measurement at scale. (24th June 2019) - Richter, Linda; Black, Maureen; Britto, Pia; Daelmans, Bernadette; Desmond, Chris; Devercelli, Amanda; Dua, Tarun; Fink, Günther; Heymann, Jody; Lombardi, Joan; Lu, Chunling; Naicker, Sara; et al.
Abstract : Experiences during early childhood shape biological and psychological structures and functions in ways that affect health, well-being and productivity throughout the life course. The science of early childhood and its long-term consequences have generated political momentum to improve early childhood development and elevated action to country, regional and global levels. These advances have made it urgent that a framework, measurement tools and indicators to monitor progress globally and in countries are developed and sustained. We review progress in three areas of measurement contributing to these goals: the development of an index to allow country comparisons of young children's development that can easily be incorporated into ongoing national surveys; improvements in population-level assessments of young children at risk of poor early development; and the production of country profiles of determinants, drivers and coverage for early childhood development and services using currently available data in 91 countries. While advances in these three areas are encouraging, more investment is needed to standardise measurement tools, regularly collect country data at the population level, and improve country capacity to collect, interpret and use data relevant to monitoring progress in early childhood development.